Proceedings of the International Conference on Science and Technology (ICST 2018) 2018
DOI: 10.2991/icst-18.2018.228
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Learning Programs at Bali State Polytechnic (BSP)

Abstract: This evaluation study aims to determine the profile of the implementation of learning programs in PNB in terms of components: 1) context, 2) input, 3) process, 4) products, and 5) linkages of learning program products with context, input and process components. The study was conducted at the Bali State Polytechnic in 2017/2018 . Object of research Student, Lecturer, Administrative Staff, and Head of department / Chair of the Study program. Research subjects were recruited proportionally stratified random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
2
0
0
1
Order By: Relevance
“…However, products and input have poor support. It validates the findings of Gunung and Darma (2018), who concluded that the execution of the teaching program is adequate in terms of context, input, process, and output. It also supports the findings of Riptiani et al (2015) and Kavgaoglu and Alci (2016), stating that the efficacy of each setting, input, process, and product determines the level of effectiveness of the program under consideration.…”
Section: Resultssupporting
confidence: 86%
“…However, products and input have poor support. It validates the findings of Gunung and Darma (2018), who concluded that the execution of the teaching program is adequate in terms of context, input, process, and output. It also supports the findings of Riptiani et al (2015) and Kavgaoglu and Alci (2016), stating that the efficacy of each setting, input, process, and product determines the level of effectiveness of the program under consideration.…”
Section: Resultssupporting
confidence: 86%
“…The context and process have strong supports, while the input and product have weak supports. It supports the result of an evaluation by Gunung and Darma (2018) that the implementation of the teaching program at BSP, viewed from the variables of context, input, process, and the product, is sufficient enough. It confirms the studies by Kavgaoglu and Alci (2016) and Riptiani, Manuaba, and Putra (2015) that the effectiveness of each component of context, input, process, and product influences the level of effectiveness of the program evaluated.…”
Section: Based Onsupporting
confidence: 68%
“…Salah satu persoalan di bidang pendidikan yang telah lama menjadi wacana publik adalah adanya kesenjangan antara kualitas SDM yang dihasilkan oleh institusi pendidikan dengan kualitas SDM yang dibutuhkan oleh DUDI. Menurut [6] fakta di lapangan saat ini mengindikasikan bahwa penyelenggaraan pendidikan dan pelatihan kejuruan berjalan dengan programnya sendiri. Pada sisi dunia kerja/industri dan asosiasi profesi sering mengeluh bahwa kualitas tenaga (lulusan) belum memenuhi tuntutan keahlian kompetensi yang diharapkan.…”
Section: Sekolahunclassified